Monopoly’s First Moment in Global Electronic Communication: From Private Monopoly to Global Media Reform, Circa 1860-1920 - Pike, Robert; Winseck, Dwayne (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractThis paper analyses the ownership, control, business practices and ideologies surrounding the creation of a global and imperial underseas cable network between the 1860s and 1920s. A major focus is placed on linkages between governments (notably Britain) and private cable cartels in the formulation of cable policies and on debates that arose between the 1880s and first decade of the twentieth century concerning private versus state ownership of cables and the issue of cable rates. In these debates, Canada was heavily involved in favour of state ownership and stronger imperial ties. The Pacific Cable seen as the first phase in the implementation of an “All Red” cable system, then Canada engaged in a short-lived campaign for reform on the Atlantic route. The paper shows the need to go beyond imperial military motives to explain the net's form and functioning; it also examines similarities between old and new patterns of globalisation in electronic communications.